Vaginal delivery is safely achieved in pregnancies complicated by spinal cord injury: a retrospective 25-year observational study of pregnancy outcomes in a national spinal injuries centre - Katherine Robertson; Rehana Dawood; Felicity Ashworth (BMC, 2020)
Abstract Background Women with spinal cord injuries (SCI) represent a high risk population during pregnancy with comparatively few studies in the literature regarding their management and pregnancy outcomes, due to the relative rarity of the condition. Our objective was to assess pregnancy outcomes in women with spinal cord injury. Methods We performed a retrospective observational study of pregnancy outcomes by reviewing maternity records of all pregnant women with SCI attending the National Spinal Injury Centre at Buckinghamshire NHS Trust between 1991 and 2016. The outcome measures were Maternal demographic data, antenatal complications, method of anaesthetic, intrapartum data (gestation at delivery, onset of labour, mode of delivery, indication for obstetric intervention) and neonatal outcomes (low birth weight, stillbirth, neonatal death). Results Fifty women with a total of 68 pregnancies were identified. Five patients sustained SCI during pregnancy and the remaining 63 pregnancies were conceived at least 1 year after SCI, of which 45 pregnancies had a SCI at T10 or above (73%) and 23 pregnancies at T11 or below (27%). The most common antenatal complications in SCI patients were worsening of spasms (38%) and urinary tract infection (24%). Preterm delivery occurred in 18% of women. Vaginal delivery was achieved in 77% of pregnancies, including 14% instrumental delivery rate and 23% Caesarean delivery rate. Conclusions Our findings support the current evidence that pregnancy outcomes are generally successful and that vaginal delivery can be safely achieved in the majority of women, independent of the level of SCI.